Changes in Proximal Femoral Shape During Fetal Development. Issue 3 (March 2019) - Li, Don T.; Cui, Jonathan J.; Henry, Havalee T.; Cooperman, Daniel R.
Abstract : Background: Walker and Goldsmith's classic article on fetal hip joint development reported that neck/shaft angle did not change from 12 weeks of gestational age through term while version increased from 0 to 40 degrees. This suggests no change in coronal alignment during development, a conclusion we dispute. By re-examining their data, we found that the true neck/shaft angle (tNSA) decreased by 7.5 degrees as version increased by 40 degrees from 12 weeks of gestational age to term. Methods: Four investigators measured both femoral version and neck-shaft angle from photographs published by the authors of femurs at multiple stages of maturation from 12 weeks of gestational age to term. The tNSAs and inclination angles were calculated for each femur illustrated using previously validated formula. Changes in the morphology of the femur over time were analyzed using a Student t test. Interobserver and intraobserver reliability were also determined by the Pearson R coefficient. Results: As reported by Walker and Goldsmith, apparent neck/shaft angle (aNSA) did not significantly change during maturation, whereas version increased by 40 degrees. However, tNSA decreased by 7.5 degrees during maturation, while the inclination increased by 32 degrees over the same period. This paper demonstrates angular changes in both the coronal and transverse planes with a 4:1 ratio of angular change in the transverse and coronal planes respectively. Interobserver Pearson coefficient R =0.98 and an intraobserver Pearson coefficient R =0.99. Conclusions: Although Walker and Goldsmith reported angular changes only in the transverse plane, we conclude that they identified angular changes in both the coronal and transverse planes. Here we show it is mathematically necessary for tNSA to decrease, if aNSA remains constant as version increases. Clinical Relevance: A reader who is not well versed in the difference between aNSA and tNSA or version and inclination cannot appreciate what Walker and Goldsmith presented. Surgeons operating on the proximal femur also benefit from understanding these distinctions.